The relevance of cardiac and gastric interoception for disordered eating behavior - Aline Tiemann; Julie Ortmann; Marius Rubo; Andrea H. Meyer; Simone Munsch; Claus Vögele; Zoé van Dyck (Journal of Eating Disorders)
Abstract Background Gastric interoception (i.e., the perception of gastrointestinal signals such as hunger, satiety or nausea) in the context of eating has recently gained increasing research attention. Nevertheless, it remains poorly understood how different interoceptive dimensions (e.g., self-report) and organ systems (e.g., cardiac, gastric) relate to each other and to disordered eating behaviors such as emotional, external and restrained eating. We assessed multiple dimensions (behavioral, self-reported, and physiological) in the cardiac domain (interoceptive accuracy, interoceptive self-report, interoceptive insight and objective physiological state) and in the gastric domain (gastric interoceptive sensitivity, gastric attribution of interoceptive sensations, interoceptive self-report, interoceptive insight and objective physiological state). The first goal of this study was to examine the relationship between cardiac and gastric interoception measured via multiple dimensions (behavioral, self-reported, and physiological). The second goal was to investigate whether multidimensional gastric interoception was a more important predictor of emotional, external and restrained eating than multidimensional cardiac interoception. Methods Our sample (n = 128) was predominantly female (n = 116), included healthy individuals (n = 87) and individuals with an eating disorder or sub-clinical eating disorder (n = 41). Instruments included a heartbeat counting task, the two-step Water Load Test, electrocardiogram, electrogastrogram and the Dutch-Eating Behaviour Questionnaire. We used correlation analysis, multiple regressions, and LASSO regressions. The final sample included in the multiple regression and LASSO regressions resulted in N = 89. Results Results showed cardiac and gastric interoception to be distinguishable, yet not to be entirely independent processes. Results further suggest gastric and not cardiac interoception to be the most important predictor of emotional, external and restrained eating. Specifically gastric attribution of interoceptive sensations played the most important role in all disordered eating behaviors. Conclusions Our findings highlight the importance of the gastric system in the assessment and targeted treatment of disordered eating behaviors. Future research should consider adding additional interoceptive dimensions.